TIMELIKE BIHARMONIC S-CURVES ACCORDING TO SABBAN FRAME IN (S12)H - Korpinar, Talat; Turhan, Essin (Editura Bibliotheca-Bibliotheca Publ House, 2012)
In this paper, we study timelike biharmonic curves according to Sabban frame in the (S-1(2) )(H..)We characterize the timelike biharmonic curves in terms of their geodesic curvature. Finally, we find out their explicit parametric equations according to Sabban Frame.
Keywords: Biharmonic curve; Heisenberg group; Geodesic curvature